Technological Innovation for the Sustainability of Knowledge and Natural Resources: Case of the Choco Andino Biosphere Reserve - Heredia-R, Marco; Falconí, Verónica; H-Silva, Jamil; Amores, Katherine; Endara, Carla A.; F-Ausay, Karina (Advances in Intelligent Systems and Computing, 2021)
The management of natural resources has multiple challenges, such as covering the needs of a population that is estimated to exceed nine billion people by 2050, Therefore, the need for a digital evolution in agriculture that meets the needs of a world population in the future is identified The objective was: evaluate the sustainability of natural resources as a contribution towards the technological innovation of agriculture; the snowball sampling technique was used, in four productive systems: mixed, agroecological, indigenous y conventional, located in the transition and buffer zones of the Choco Andino Biosphere Reserve, SAFA evaluation framework (FAO) was used. The data were collected through a semistructured interview based on a questionnaire of 117 questions; the interview lasted 75–85 min conducted to the heads of household In the results were evidence of the 12 case of studies and the different sustainability dynamics in the dimensions: good governance, economic residence, environmental integrity and social welfare. The similar characteristic between case studies was the precarious capacity to govern natural resources, which strengthens the importance of intervention with a digital literacy process to improve management capacity.
Keywords: digital technology; rural territories; SAFA; Scopus(2)